ASSOCIATION OF AGE AND GENDER PREVALENCE IN PATIENTS UNDERGOING AESTHETIC CORRECTIONS USING VENEERS - Choudhari, Sahil; Sharma, Subash; Ramamurthy, Jaiganesh (International Journal of Psychosocial Rehabilitation, 2020)
Aim: The aim of the study was to find out the association between the age and gender distribution in patients undergoing veneering treatment.Materials and Methods: Patients who reported for esthetic management of teeth and for whom veneering treatment had been done in Saveetha Dental College and Hospitals, Chennai, from June 2019 to March 2020 were recruited. A total of 156 direct and indirect veneers were done among the reported patients. Data regarding age, gender, tooth number, and reason (spacing, discoloration, or both) for the need of esthetic treatment were collected and analyzed.Results: Out of 156 patients, most (71.2%) of the patients belonged to the age group between 20 and 40 years. Gender distribution of patients showed 37.8% of the patients were females and 62.2% of the patients were males. 48.7% of the patients reported with the complaint of spacing Also, associations between gender and reason for veneering treatment and age and reason for veneering treatment were found to be statistically significant.Conclusion: Within the limitations of the study, the age group between 20 and 40 years reported the maximum for veneering treatment (71.2%). Among the genders, males (62.2%) reported a higher incidence than females (37.8). Spacing (48.7%) was the most common reason for patients undergoing veneering treatment.